A Novel Method for Primary Blood Cell Culturing and Selection in Drosophila melanogaster - Enikő Kúthy-Sutus; Bayan Kharrat; Erika Gábor; Gábor Csordás; Rita Sinka; Viktor Honti (Cells, 2022)
The blood cells of the fruit fly Drosophila melanogaster show many similarities to their vertebrate counterparts, both in their functions and their differentiation. In the past decades, a wide palette of immunological and transgenic tools and methods have been developed to study hematopoiesis in the Drosophila larva. However, the in vivo observation of blood cells is technically restricted by the limited transparency of the body and the difficulty in keeping the organism alive during imaging. Here we describe an improved ex vivo culturing method that allows effective visualization and selection of live blood cells in primary cultures derived from Drosophila larvae. Our results show that cultured hemocytes accurately represent morphological and functional changes following immune challenges and in case of genetic alterations. Since cell culturing has hugely contributed to the understanding of the physiological properties of vertebrate blood cells, this method provides a versatile tool for studying Drosophila hemocyte differentiation and functions ex vivo.